The persistence of neighborhood disadvantage: an experimental investigation of alcohol and later physical aggression - Topalli, Volkan (Criminal justice and behavior, 2014)
This research examined the combined impact of alcohol and previous experience growing up in a disadvantaged neighborhood on aggression in a laboratory setting. Participants were 505 young adult social drinkers between 21 and 35 years of age who completed a retrospective measure of neighborhood disadvantage and then participated in an experimental procedure, where they either consumed an alcohol or placebo beverage. They were subsequently tested on a laboratory aggression task in which they were provoked by receiving electric shocks from a fictitious opponent under the guise of a competitive reaction-time task. Aggression was operationalized as shock intensities and durations administered, in retaliation, by the participants to their fictitious opponent. Acute alcohol intoxication significantly increased aggression for those who grew up in disadvantaged neighborhoods. Thus, our investigation supports Sampson?s notions of ?legacies of neighborhood inequality? with important implications for the etiology and prevention of violence in real-world settings.